2009
DOI: 10.3354/meps08166
|View full text |Cite
|
Sign up to set email alerts
|

Multi-century time-series of 15N and 14C in bamboo corals from deep Tasmanian seamounts: evidence for stable oceanographic conditions

Abstract: Bamboo corals (Family Isididae) are an important component of seamount benthos south of Tasmania. Besides having lifespans of up to 400 yr, little is known about their basic ecology, nor how to decode potential climate signals encoded in their skeletons. We explored the stable nitrogen isotope and radiocarbon compositions of the skeletal organic fraction of the genera Isidella, Keratoisis and Lepidisis collected from 3 Tasmanian seamounts. Analyses were performed on tissues and organic node growth rings sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The cause of this difference is not clear, but one possibility is that it reflects differences in food availability. Surface productivity tends to be high in the NE Pacific relative to most other parts of the world's oceans (Koblentz-Mishke et al 1970), and isotopic evidence indicates that bamboo corals feed on suspended matter derived from surface production (Roark et al 2005, Sherwood et al 2009, in this Theme Section). However, surface productivity also tends to be high in the NW Atlantic, for which colony growth rates are close to or even slightly lower than predicted.…”
Section: Discussionmentioning
confidence: 94%
“…The cause of this difference is not clear, but one possibility is that it reflects differences in food availability. Surface productivity tends to be high in the NE Pacific relative to most other parts of the world's oceans (Koblentz-Mishke et al 1970), and isotopic evidence indicates that bamboo corals feed on suspended matter derived from surface production (Roark et al 2005, Sherwood et al 2009, in this Theme Section). However, surface productivity also tends to be high in the NW Atlantic, for which colony growth rates are close to or even slightly lower than predicted.…”
Section: Discussionmentioning
confidence: 94%
“…Although saturation levels in those studies are considerably higher than those experienced by the deep-sea taxa we observed, the principle that elevated food availability could compensate for the higher costs of calcification in heterotrophic deepsea species appears plausible. Radiocarbon and 15 N studies show that to depths of at least 1000 m, bamboo corals consume sinking particulate organic carbon (Sherwood et al 2009). A similar food source has been speculated for other deep-water corals (Roberts et al 2009).…”
mentioning
confidence: 99%
“…These results are consistent with previous studies that used the HCl pretreatment to remove calcite in the Primnoa sp. skeleton (e.g., Sherwood et al, 2009, Williams et al, 2007b. While the standard 5% acidification pretreatment did significantly alter octocoral skeleton bulk δ 13 C values, it did not significantly impact the δ 13 C values of the individual AAs that make up that bulk material (Table 2).…”
Section: Experiments One: Pretreatment Effectmentioning
confidence: 99%